Planʺ gavani Kuėgda, po glazomi︠e︡rnoĭ sʺëmki︠e︡ 1869 goda Leĭtenanta Starit︠s︡kago / Kopirovalʺ khimicheskoi︠u︡ tushʹi︠u︡: V. Akovenkovʺ. Korrektirovalʺ Podporuchikʺ Bri︠a︡nt︠s︡evʺ - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департмент, 1869)
Relief shown by form lines. Depths shown by soundings and isolines.; Title translation: Plan of Kuegda Harbor, according to the 1869 survey by Lieutenant Staritsky.; Margin title translation: Sea of Okhotsk. Northern coast of Sakhalin Island.; Oriented with north to the upper right.; "No. 289" -- handwritten bottom right margin Grayscale;